PENGARUH KETERIKATAN PEGAWAI DAN KEPRIBADIAN INDIVIDU TERHADAP PERILAKU PEGAWAI KONTRAK DI SEKRETARIAT DAERAH KOTA SOLOK - Megawirva Komala; Nurhayati Nurhayati (LP2M Universitas Bina Bangsa, 2022)
This study aims to find out how much influence Employee Attachment and Individual Personality have on the Behavior of contract employees in the Regional Secretariat of Solok City. In this study, the population was contract employees who numbered 40 people. With quantitative research types and sampling techniques using purposive sampling methods. The data collection technique used is to use questionnaires. Based on multiple linear regression analysis of the variables Employee Attachment and Individual Personality affects the Behavior of contract employees in the Regional Secretariat of Solok City Y = 3.922 + 0.735X1 + 0.173X2 + e. From the t test conducted, it was obtained that the variable X1 Employee Attachment had a significant effect on Employee Behavior with a t count greater than t table 9.940 > 2.026 and a significant level value of 0.000 < α 0.05 then H0 was rejected and H1 was accepted. Variable X2 Individual Personality had a significant effect on Employee Behavior the calculated value of t was known > t table which was 2.150 > 2.026 and the significance value was 0.038 < 0.05 then H0 was rejected and H2 was accepted. From the f test conducted, it was found that Employee Attachment and Individual Personality had a simultaneous effect on Employee Behavior with f counting 76.707 > f table 3.24 with a significance value of 0.000 < 0.05 then H0 was rejected and H3 was accepted. From the Determination Test, the R square value was 0.806 or 80.6%. This indicates that the contribution of the variables Employee Attachment and Individual Personality is 80.6%. While the remaining 19.4% is influenced by other variables